Direct Digital Frequency Synthesizer Designs in MATLAB - YUNUS EMRE ACAR; Ercan YALDIZ (International Journal of Applied Methods in Electronics and Computers, 2016)
This study presents the structure of the Direct Digital Frequency Synthesizers (DDFSs) which have several advantages compared to conventional synthesizers such as high frequency, fast switching speed and low power dissipations. In order to lessen the physical area and power dissipation, ROM compression techniques are applied in designs. Bipartite Table Method (BTM) and Multipartite Table Method (MTM) are utilized in this study because of the fact that they provide high compression rates. By using MTM, the compression rates of 157.54:1, 726.71:1 and 3463.29:1 are obtained at 58.40 dB, 75.30 dB and 84.66 dB SFDR levels, respectively.